Genome Sequence Comparison and Scenarios for Gene Rearrangements: A Test Case - Sridhar Hannenhalli; Chappey, Colombe; Koonin, Eugene V.; Pevzner, Pavel A. (GenomicsGenomics, 1995)
As large portions of related genomes are being sequenced, methods for comparing complete or nearly complete genomes, as opposed to comparing individual genes, are becoming progressively more important. A major, widespread phenomenon in genome evolution is the rearrangement of genes and gene blocks. There is, however, no consistent method for genome sequence comparison combined with the reconstruction of the evolutionary history of highly rearranged genomes. We developed a schema for genome sequence comparison that includes three successive steps: (i) comparison of all proteins encoded in different genomes and generation of genomic similarity plots; (ii) construction of an alphabet of conserved genes and gene blocks; and (iii) generation of most parsimonious genome rearrangement scenarios. The approach is illustrated by a comparison of the herpesvirus genomes that constitute the largest set of relatively long, complete genome sequences available to date. Herpesviruses have from 70 to about 200 genes; comparison of the amino acid sequences encoded in these genes results in an alphabet of about 30 conserved genes comprising 7 conserved blocks that are rearranged in the genomes of different herpesviruses. Algorithms to analyze rearrangements of multiple genomes were developed and applied to the derivation of most parsimonious scenarios of herpesvirus evolution under different evolutionary models. The developed approaches to genome comparison will be applicable to the comparative analysis of bacterial and eukaryotic genomes as soon as their sequences become available.